Activation of Cement Clinker as Catalysts for Transesterification Reaction of Palm Oil Off Grade to Biodiesel - Putri, Karina Octaria; Miftahudin, Dhani Nur; Helwani, Zuchra; Bahri, Syaiful (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
Calcium oxide (CaO) is a heterogeneous solid base which is generally used as a catalyst in making biodiesel. It is mainly obtained from cement clinker and activated through calcination method. The purpose of this study was to determine the effect of using cement clinker catalyst on the yield of the biodiesel. A batch reactor with a condenser was used in making the biodiesel under favorable conditions such as calcination temperatures of 700 C, 750 C and 800 C, time of 5, 6 and 7 hours, and catalyst concentration of 1%-w, 2%-w, and 3%-w oil. The analysis involved X-Ray Diffraction (XRD) and Brunauer-Emmett-Teller (BET) for catalysts and Gas Chromatography-Mass Spectrometry (GC-MS). The catalyst calcination temperature determined the optimum conditions. From this study, the conditions necessary for transesterification reaction include the mole ratio of methanol/oil of 6 to 1, the temperature of 70 C for 2 hours and 700 C for 5 hours, and catalyst dosage of 2% by weight. Under these conditions, the yield of the biodiesel was 84.26%. Additionally, at the calcination temperature of 800 C for 7 hours and catalyst dosage of 3% by weight, the yield of the biodiesel was 76.84%. CaO, SiO2, 2CaO.SiO2 and 3CaO.SiO2 were found in the catalyst through XRD analysis. The specific surface areas of the catalyst were 25,497 m2/g (700 C/5 hours) and 35,879 m2/g (800 C/7 hours) through BET analysis. According to the GC-MS analysis, the main components of the biodiesel include methyl palmitate, methyl oleate, and methyl stearate.